High-stability solid solution perovskite (1-x) Bi0.2Sr0.5La0.3TiO3- xLaMnO3 (0.05≤ × ≤0.2) for wide-temperature NTC thermistors - Liu, Ting; Yang, Guanghua; Ma, Juan; Zhang, Huimin; Zhang, Min; Chang, Aimin (Frontiers in Chemistry, 2023)
The development of negative temperature coefficient (NTC) thermistor materials with a wide range of operating temperatures, high resistance (R), low thermal content (B) and good stability is significant for improving the overall performance of NTC thermistors. Traditional NTC thermistors materials are of the spinel, however,their practical applications are commonly limited to temperatures below approximately 200 °C.In this study, it was found that a novel perovskitestructured solid solution (1-x)Bi0.2Sr0.5La0.3TiO3-xLaMnO3 (0.05≤x≤0.2) (BSLT-LM) showed good NTC performance from room temperature to high temperature (600℃) due to the stable structure at high temperatures. The ρ25, ρ100, ρ600 and B25/100, B25/600 constants of Bi0.2Sr0.5La0.3TiO3-0.1LaMnO3 NTC thermistors are approximately 1.76×10 8 Ω cm, 1.13×10 7 Ω cm, 9.89×10 2 Ω cm, 4063.91 K, 5472.34 K, respectively. The electrical conductivity of these solid solution refers to the electronic transition between Mn 3+ and Mn 4+ , and oxygen vacancies. These results demonstrate the tremendous potential of perovskite-structured (1-x) Bi0.3Sr0.5La0.2TiO3-xLaMnO3 thermistor ceramics with NTC performance.